هل كان ابن تيمية فيلسوف ً ا اسميا؟ دراسة تحليلية نقدية في قراءة أبي يعرب المرزوقي البن تيمية = Was Ibn Taymiyyah a nominalist? a critical analytical study of Abu Yarub Al Marzouqi’s reading of Ibn Taymiyyah - Muhamad Shukri, Abdul Salam; Al–Samhouri, Raed (Doha Institute of Graduate Studies & Arab Research for Policy Studies, 2020)
Abu Yarub Al Marzouqi believes that the famous Hanbalite scholar Ibn Taymiyya adopts a nominal methodology, Indeed, that he sees Islam – which he calls «Neo–Hanafism» – as a nominalist project used to confront the realism adopted by the neo–Platonists as regards their view of Universals: can the universal be verified in reality, or is it an exclusively mental concept? Since Ibn Taymiyya is clearly inclined towards the belief that it is a solely mental concept, as the study shows, the real point of discussion is: does Ibn Taymiyya believe this mental concept is congruent with the specifics of the external world as his writings suggest or not as Marzouqi suggests? This critical study lays out Marzouqiʼs reading of Ibn Taymiyya and raise the question: does the Marzouqi reading seek precision or is it a projection that does not correctly express Ibn Taymiyya’s approach to the «universal» and its congruence with external particulars?